THE INFLUENCE OF MINDFUL THOUGHT ON EMOTIONAL REGULATION IN ADULTS: A LITERATURE REVIEW - Haryati Septiani; Meidiana Dwidiyanti; Megah Andriany (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Mental disorder is one of the most difficult problems to overcome in the world and one of the causes is about the low emotional regulation. Emotional regulation is influenced by a person's awareness in managing his emotions. For increasing the emotional regulation need some interventions to enhance mindful thought and the benefits will appear. Objectives: This article aimed to explain the benefits of mindful thought in emotion regulation and the type of intervention can be used to improve mindful thought in adults. Design: This study used a scoping review to review the articles the influence of mindful thought on emotional regulation in adults. Data Sources: Data based used were Science Direct, Scopus, SpingerLink, PubMed and Emerald Insight from 2017 to 2021. The literature obtained by using the Booleon operators “OR/AND” search. The keywords in the search were "mindfulness" OR mindfulness breathing AND "emotion regulation" OR control emotion AND "adult". Review Methods: The analysis used was the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes for Scoping Review (PRISMA-SR). Results: The results after screening consisting of 4 quantitative articles. This article summarizes about mindfulness intervention can increase the ability to respond to negative emotions, reduce depression, stress and also increase important components in mindful thought that can influence emotional regulation. Conclusion: High level of mindful thoughts will influence daily life in adults for reappraisal, acceptance, problem solving and parenting. The kind of mindfulness intervention can be used for increasing quality of mindful that can affect emotion regulation in adults such as Mindfulness Meditation, Mindfulness Based Cognitive Therapy and Mindfulness Based Stress Reduction.